The system of functioning of the sports federations, depending on structural and financial indicators - Darko Mitrović; Željko Rajković; Vladimir Miletić; Aleksandar Kovačević (University of Banja Luka, Faculty of physical education and sport, 2019)
Sports clubs are the bearers of sport development in every community. The Municipal Sports Associations in Serbia (e.g. municipality of Mionica) recorded very poor results in an overview of regular physical exercise among the general population. Indeed, 96.45% of the residents of the municipality of Mionica do not exercise regularly. Of the total number, 88.7% of Mionica's population lives in rural areas. Estimates put approximately 1,000 Mionica's residents per one sport club. The municipality annually allocates only 445 dinars (3.7 euros) for sports per resident. Considering the financial constraints, administrative and HR-related solutions were proposed in order to increase the population's participation in sports activities. For more significant changes, urgent, active action is needed in terms of cooperation between all sports organizations, in addition to the health, educational and business organizations on a local level. Offered activities must rely on the interest of the population and their tradition. In the newly envisioned system, the Secretary General of the Municipal Sports Association would have the active leading role, with greater authority, as well as performance-based funding. The newly defined model for sports organization on the territory of the municipality needs to be researched in practice, so as to examine the pros and cons of the new system.